ADITIVO AROMATIZANTE EM SUPLEMENTO MINERAL NA RECRIA DE BOVINOS DE CORTE MANTIDOS EM PASTAGEM - THAINÁ ARRUDA DE CARVALHO (2024)
The aim of this study was to evaluate two concentrations of flavoring in mineral supplements on supplement consumption, trough behavior and performance of beef cattle kept on pasture. Four experiments were carried out, with two concentrations of NaCl in the formulation (43% and 20%). Experiments 1 and 2 were carried out at a concentration of 43% NaCl in the mineral supplement formulation (SM; 161 g Na/kg). Experiment 1: SM with flavoring at a dose of 750 g/ton (T750) versus SM without flavoring (Control). Experiment 2: SM with flavoring at a dose of 500 g/ton (T500) versus SM without flavoring (Control). Experiments 3 and 4 repeated the treatments of experiments 1 and 2, but with the inclusion of 20% NaCl (74 Na/kg of SM). 80 Nelore steers (11 ± 2.5 months) were used, divided into four batches of 20 animals each, allocated to Brachiaria brizantha cv. Marandu pasture. Behavior was monitored using a Radio Frequency Identification (RFID) system. A completely randomized design was used and the means were compared using the PDIFF test at a 5% significance level. In experiments 1 and 2, there were no differences in supplement consumption between treatments. In experiment 1, the animals in batch T750 made more visits to the SM trough per week compared to the Control (P = 0.009; 13.3 and 7.5 visits/animal/week, respectively). In experiment 2, T500 had higher GMD than the Control (P = 0.040; 0.36 and 0.28 kg/animal/day, respectively). In experiment 3, there was no difference in consumption, and in experiment 4 there was higher consumption for T500 x Control (P = 0.006; 81.2 and 62.5 g/animal/day, respectively). In experiment 3, the number of visits to the trough was higher in T750 x Control (P < 0.001; 24.4 and 4.9 visits/animal/week, respectively) and also in experiment 4, T500 x Control (P < 0.001; 27.1 and 8.1 visits/animal/week, respectively). Higher GMD was observed in experiment 3, T750 compared to Control (P = 0.006; 0.38 and 0.31 kg/animal/day, respectively). The use of flavorings improved trough behavior, attracting more animals to the supplement trough during the week. With the reduction in sodium, there was a positive effect of the flavoring on increasing supplement consumption. The flavoring favored better animal performance when forage was limited.